Prevalence of hypocalcemia in four grazing Jersey herds in Costa Rica - Sánchez, Jorge Ml. (2014)
Clinical hypo-calcemia (CH) is a common metabolic disease in cows grazing lush pastures high in potassium. The aim of this study was to determine the prevalence of CH and subclinical hypocalcemia (SH) in 4 grazing Jersey herds in Costa Rica. Subclinical hypocalcemia has been studied to a limited extent in tropical dairy systems. Two hundred and seven Jersey cows from 4 herds located in the highlands of Cartago, Costa Rica, were used to analyze serum calcium (Ca) contents. Feeding practices during the close up period were based on intensive grazing of kikuyu grass (Kikuyuocloa clandestina) and the supplementation of 3 to 4 kilograms of a grain mixture low in Ca (0.2% of dry matter). Blood samples were arranged by lactation number: 1st (n=36), 2nd (n=48), 3rd (n=49), 4th (n=41), 5th (n=17) and 6th (n=16). Average serum Ca concentration within the criti- cal period for hypocalcemia incidence (24 h befo- re or after parturition) decreased with lactation number. Incidence of CH was 6, 13, 2, 29, 29 and 25% of cows from 1st to 6th parity, respectively. Likewise, average prevalence of SH was 53, 42, 78, 44, 47 and 63%, in the same order. Cows with a body condition score (BCS) of 3.75 or higher at parturition ± 1 week had lower (p<0.05) serum Ca concentration than those with lower BCS. Serum magnesium contents were normal. These results show that prevalence of SH is greater than 40% in Jersey herds grazing lush tropical pastures; also, data suggest that BCS during the transition period could influence serum Ca contents. However, more research should be done to support these findings.